Les fonctions internes de la détente dans les systèmes politiques du triangle euro-arabo-africain : l’image oubliée de l’interdépendance Nord-Sud - Laabi, Abdelhai (Études internationales, 1980)
This study deals with two increasingly important aspects of international relations : first, the interpretation of the North-South dynamic of the international System and second, the significance of détente in the Euro-Arabo-African mini-triangle.In his discussion of the first problematic, the author suggests it would be useful to take an interdependence approach towards the analysis of North-South relations, implying that the international system is hexagonal as regards both structure and process and that non-alignment is becoming a sixth pole of influence in the system. More specifically, and taking as a starting point the « depolarization » of the détente process, the author argues that the security objectives of the West European, Arab and African political Systems are in fact interdependent. This interdependence is to be found above all in their interest in diluting the East-West conflict and instituting a policy of détente, the purpose of which is all the more significant for being internal - i.e. the stabilization, legitimization and integration of these political Systems. Since the effects of such a policy will be felt only gradually, these countries find they have a common interest in a complementary strategy whereby the East-West conflict is segmented and intersected by the North-South conflict (intra-alliance, even).The aim of the study is to show that, in the theory of international relations, greater attention should be paid to the motivations and strategies of actors in the South and their impact on the international system in the economic problem areas as well as the political and strategic ones.Because the properties of political reality differ from those of physical reality, the properties of political regularities also differ from those of physical regularises. The regularities we discover are soft. They are soft because they are outcomes of processes that exhibit plastic rather than cast-iron control. They are imbedded in history and involve recurrent « passings-through » of large numbers of human memories, learning processes, human goal seeking impulses, and choices among alternatives. They decay quickly because of the memory, creative searching, and learning that underlie them. Indeed social science itself may contribute to this decay, since learning increasingly include not only learning from experience, but from scientific research itself. Gabriel A. ALMOND et Stephan J. GENCO, « Clouds, Clocks, and the Study of Politics », World Politics, vol. XXIX, n° 4, juillet 1977, pp. 493-494. Ithas become a platitude that the whole world is now interdependent... Yet what a tremendous platitude it is /... If this platitude is unalterably true, its implications must profoundly affect the conditions of human life for the future ; it must transform all our thinking about social organization ; it must modify all our programmes and policies. Clearly we ought to be thinking seriously about it, and asking ourselves what it involves. A. MuiR, The Interdependent World and lts Problems, Boston, Houghton, Mifflin, 1973, p. 1.